RTEL1 tagging SNPs and haplotypes were associated with glioma development - Li, Gang (BioMed Central, 2013)
ABSTRACT: As glioma ranks as the first most prevalent solid tumors in primary central nervous system, certain single-nucleotide polymorphisms (SNPs) may be related to increased glioma risk, and have implications in carcinogenesis. The present case–control study was carried out to elucidate how common variants contribute to glioma susceptibility. Ten candidate tagging SNPs (tSNPs) were selected from seven genes whose polymorphisms have been proven by classical literatures and reliable databases to be tended to relate with gliomas, and with the minor allele frequency (MAF) > 5% in the HapMap Asian population. The selected tSNPs were genotyped in 629 glioma patients and 645 controls from a Han Chinese population using the multiplexed SNP MassEXTEND assay calibrated. Two significant tSNPs in RTEL1 gene were observed to be associated with glioma risk (rs6010620, P = 0.0016, OR: 1.32, 95% CI: 1.11-1.56; rs2297440, P = 0.001, OR: 1.33, 95% CI: 1.12-1.58) by χ(2) test. It was identified the genotype “GG” of rs6010620 acted as the protective genotype for glioma (OR, 0.46; 95% CI, 0.31-0.7; P = 0.0002), while the genotype “CC” of rs2297440 as the protective genotype in glioma (OR, 0.47; 95% CI, 0.31-0.71; P = 0.0003). Furthermore, haplotype “GCT” in RTEL1 gene was found to be associated with risk of glioma (OR, 0.7; 95% CI, 0.57-0.86; Fisher’s P = 0.0005; Pearson’s P = 0.0005), and haplotype “ATT” was detected to be associated with risk of glioma (OR, 1.32; 95% CI, 1.12-1.57; Fisher’s P = 0.0013; Pearson’s P = 0.0013). Two single variants, the genotypes of “GG” of rs6010620 and “CC” of rs2297440 (rs6010620 and rs2297440) in the RTEL1 gene, together with two haplotypes of GCT and ATT, were identified to be associated with glioma development. And it might be used to evaluate the glioma development risks to screen the above RTEL1 tagging SNPs and haplotypes. VIRTUAL SLIDES: The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1993021136961998